LEARNING DIFFERENT READING STRATEGIES AS A BASIS FOR LEARNING SKILLS - Āboltiņa, Līga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Based on the latest OECD International Studies (The Organisation for Economic Co-operation and Development [OECD], 2019) on reading literacy of Latvian primary school pupils, the overall reading literacy has fallen.The ability to read and understand text is one of the first skills students need at school. Based on observations during practice, primary school learners are technically well literate, that is, they can clearly read what has been written, acknowledge sentence boundaries, and read with appropriate intonation. However, the task of the school is not to teach students to read technically, but to read thoughtfully, so that the information could be understood and used in further learning activities. Literacy is not just about drawing letters and stringing them together; it is about developing an interest in reading, as well as the quality of cognitive processes. Learning diverse reading strategies in the primary school curriculum is a way of stimulating students' interest and thinking ability, and their ability to learn in a self-directed way.The aim of the study is to analyse the experience of a school teachers’ team, encouraging pupils' reading proficiencies in order to develop the pupil as a skilled reader during the learning process.Research methods: literature and source analysis, survey method - questionnaire, obtained data processing and analysis, performance analysis. The results of the study show that mastering diverse reading strategies in the primary school curriculum is a way to enhance students' thinking and self-directed learning capabilities.